Akulturasi dalam Arsitektur Jawa di Yogyakarta: Fasade berpedimen dalam Arsitektur Jawa di Kraton Yogyakarta dan Dalem Notonegaran - Hendria Bagja Prasthia; Putu Ayu P. Agustiananda; Revianto Budi Santosa (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: Acculturation of Javanese Architecture in Yogyakarta; Pedimented façades in Javanese architecture at the Kraton Yogyakarta and Dalem Notonegaran At the beginning of the 20th century, European Colonialism dominated almost all parts of the world. In this period, cultural acculturation was developed between European and local cultures in the colonised territory, including architecture. Many studies concerning architectural acculturation in the late colonial era emphasised the roles of European agents in appreciating while dominating the local culture. This research presents an alternative perspective by focusing on the Javanese elite as the agents of cultural change. Javanese architecture, on the one hand, with its long tradition, has recognisable stylistic formulation. On the other hand, it has a great degree of adaptation, giving chances for acculturation with many other architectural traditions. At the beginning of the 20th century, one exciting dynamic was the façade with pediment incorporating European Neo-Classical architecture. Originating in Ancient Greek Architecture, pediments continuously developed as a reference in European architecture. In Yogyakarta, the aristocratic circle adopted a pedimented façade supported by twin columns on both ends combined with many elements of Javanese culture. This research compares several pedimented façades with various cultural sources and architectural compositions in several buildings in the Sultan’s Palace of Yogyakarta and the princely residence of Notonegaran. From this comparison, this research discovers the progressive sides of Javanese architecture with many novel syntheses incorporating European architectural elements and Javanese ornamentations with novelty in composition, technology, and representation.